Education 4.0: Robotics Projects to Encourage 21st Century Skills - Eive dos S. Silva, Deivid; de Oliveira Sousa, Aline; R. Oliveira, Marcela; Corrêa Sobrinho, Marialina; Todt, Eduardo; Malveira C. Valentim, Natasha (RENOTE, 2021)
Education 4.0 is defined as a student-centered learning model that prepares young for the challenges of the 21st Century, how to deal with emerging technological resources and processes. This case study aimed to encourage 21st Century skills and competencies seen as relevant to Education 4.0, such as teamwork, communication, autonomy, creativity, and innovation. In this study, we analyzed the feedbacks collected to identify which skills were encouraged in undergraduate and graduate students during one semester of the Mobile Robotics discipline, using Project-Based Learning (PBL). Students carried out projects and answered a self-assessment questionnaire about their skills. The qualitative analysis of the case study followed the procedures of the Grounded Theory method. The results indicated that learning based on robotics projects could encourage teamwork, communication, and organization skills.